2018
DOI: 10.7202/1053867ar
|View full text |Cite
|
Sign up to set email alerts
|

Des stages en français pour se préparer à travailler auprès des communautés francophones en situation minoritaire

Abstract: Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire (CFSM), des stages en français ont été offerts à des étudiantes et étudiants bilingues de programmes de formation professionnelle offerts en anglais au sein d’universités canadiennes. L’expérience a été positive pour l’ensemble des parties prenantes : stagiaires, éducatrices-cliniciennes et responsables de la formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…As hypothesized, learning in a minoritized second language appears to be associated with anxiety. Others have suggested that the linguistic minority context may be challenging for students in French-language universities in both academic and clinical settings (Savard et al, 2018). A limited number of studies have explored the role of self-efficacy in higher learning in a second language (Peguret, 2014;Raoofi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As hypothesized, learning in a minoritized second language appears to be associated with anxiety. Others have suggested that the linguistic minority context may be challenging for students in French-language universities in both academic and clinical settings (Savard et al, 2018). A limited number of studies have explored the role of self-efficacy in higher learning in a second language (Peguret, 2014;Raoofi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is especially concern for the number of Francophone physicians who are specialists rather than general practitioners (Savard et al, 2020). Another issue is that monolingual services are not confined solely to general healthcare services, but also social and mental health services (Savard et al, 2013;Savard et al, 2018). These findings present not only an issue that has spanned over many years, but that is widespread across many different provinces and territories, and through different health and disability services.…”
Section: Monolingual English Healthcare Servicesmentioning
confidence: 99%
“…The lack of French services demonstrates that the healthcare system places little value on offering bilingual services (Savard et al, 2020). Employers do not encourage or do not support employees to continually offer services in French due to lack of perceived importance (Savard et al, 2018). For example, there is a low awareness and use of interpreter services by healthcare professionals (de Moissac & Bowen, 2017;Giguère & Conway, 2014;Ngwakongnwi et al, 2012).…”
Section: Low Importance For Bilingual or French Servicesmentioning
confidence: 99%
See 2 more Smart Citations